The Future of Mixed Tropical Hardwoods-an Important Renewable Natural Resource - Thangam, B. S. (Indian Forester, 1981)
Wood as a renewable natural resource has been compared with other non-renewable natural resources and the conservation of non-renewable resourcos by increasing wood supplies through growing forests which produce wood has been stated. The tropical moist forests occupy 64.8 million hectares out of a total forest area of 75.4 million hectares and the important hardwoods that occur in these forests have been indicated. The general increasing trend in production of wood till now has been mentioned and total industrial wood production with details for hardwoods for end-use as pulpwood, sawnwood and sleepers, panel product and roundwood have been given. The inadequacy of available consumption data has been indicated. The parameters that require consideration in projecting future demands of hardwoods are population growth, economic growth, linked with rate of raw material usage, effect of technological development, and recent predilection with environment and the interaction of these. The National Commission on Agriculture has estimated the total requirements of Industrial wood and hardwoods as 25.552 and 20.605 million m3 respectively for 1980 and 40.708 and 31.649 million m3 respectively for 1990. The strategy to produce these quantities of timber should be the conversion of the existing productive hardwood forests of 30.265 million hectares into more valuable plantations of commercially important hardwood and quick growing species. In this process, large quantities of firewood and material for pulp as wood chips would be available. The necessity to take up such large scale plantations by forming corporations with the help of institutional finance has been stressed. The technological advances made in timber utilisation, including the work done by Preinvestment Survey and Logging Training Centre have been mentioned. The social aspect of forests in providing recreation and regulating environmental factor has been brought out. By implementing this crash programme of man-made forests, India would be in a position to export large quantities of timber by 1990, after fully meeting country's demands. The future of mixed tropical hardwood is, thus, quite bright.